The implementation of food education actions in a long-term institution: an experience report (Research, Society and Development, 2020)
Aging is a dynamic and progressive process, altered by morphological, physiological, biochemical and psychological changes in individuals. Commonly, observe if there is no abandonment or abandonment process that accommodates many elderly people, who are responsible for singular multiprofessional care. Thus, in many cases, they are taken to long-term care facilities for specialized care. Check for gaps in basic food aspects within this assistance, such as food education, which is essential for the target audience. This objective study describes educational activities using music tools at a long-term care institute for the elderly. It is a descriptive research with a qualitative approach, in the form of an experience report on the theoretical-practical experience developed in a long-term institution for the elderly by nursing and nutrition students, adhering to the Methodology methods by the Arco de Maguerez. As a result, it was seen that the elderly are idle for not interacting with local people, in addition to knowledge of practical eating practices. Group interaction activities were carried out with a knowledge approach, taking nutritional guidelines. The actions carried out had their objectives achieved, as they provided the elderly with active participation and new perspectives on the importance of food consumption in the elderly, in addition to promoting palliative resources to direct feelings of idleness. Therefore, the importance of academic nursing and nutrition training in this type of action is emphasized, as it promotes individual and collective growth, as an aid in building interactions and using a holistic and welcoming look.